GREEN CONCRETE ROAD DESIGN USING FURNACE SLAG AND FLY ASH - ALHDEDY , RAFEAA M.; MUHMOOD, ABDULBASIT ABDULAZIZ (Journal of Duhok University, 2023)
Green concrete is important in low energy & resource consumption, no environmental pollution & sustainable development. Green cement concrete is produced by using recycled waste materials such as activated fly ash, slag, and the results were assessed against reference concrete. This pavement approach uses slabs of reinforced concrete or cement concrete to create stiff pavement that is more stable. Promoting the usage of concrete made from optimized fly ash pavement can end the asphalt pavement's monopoly over heavy-duty highways and significantly reduce the amount of industrial wastes, including fly ash and blast furnace slag, In changed concretes cement had been, replaced by the weight of (FA) three test groups were constituted is the replacement of percentages as: 0% (fa-00), 20% (fa-20) and 30% (fa-30). Moreover, the findings were paired with concrete's performance on roads to examine the mechanism underlying the very durable fly ash pavement concrete's design. The experiments were carried out after (3, 7, 28, 90, 180, and 365) days of curing. Cement is replaced by from different weast, both blast furnace slag and fly ash. It has been established that, if the identical working performance goals are met, optimized fly ash concrete pavement may be utilized in place of asphalt pavement. The percentages of slag substitution by cement are (30%, 40% and 50%) by weight. Mechanical, physical, and environmental properties have been evaluate. The main mechanical properties—compressive and flexural strength were analyses; density and porosity tests were reported and analyses; and an environmental leachate study was conducted.